Katalog der in den Sammlungen des ehemaligen Deutschen Entomologischen Institutes aufbewahrten Typen - XII (Coleoptera: Carabidae). - Döbler, Helga (Contributions to Entomology = Beiträge zur Entomologie, 1975)
A catalogue of the type specimens of the family Carabidae in the collections of the former Deutsches Entomologisches Institut is published.